Preparation method of complete and fine recrystallized Mg-Y-Zn magnesium alloy

Through two cumulative large extrusion ratio extrusion deformation processes, high-density fine 14H-LPSO structural phases are dynamically precipitated, solving the problem of mismatch between strength and toughness of Mg-Y-Zn-type deformed magnesium alloy, achieving complete and small recrystallization structure formation and improvement of magnesium alloy performance.

CN119571228AInactive Publication Date: 2025-03-07ZHONGBEI UNIV

Patent Information

Application Number
CN202510138000.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to improve strength and toughness at the same time for Mg-Y-Zn-based deformed magnesium alloys, and it is difficult to obtain complete and small recrystallized structures in the existing plastic deformation technology, resulting in a mismatch between strength and toughness.

Method used

Two-pass cumulative large extrusion ratio extrusion deformation process is used, and small extrusion ratio extrusion is performed first, followed by large extrusion ratio extrusion. By dynamically precipitating high-density fine 14H-LPSO structures with respect to grain boundary migration, it has a pinning effect, and overcomes the problem of recrystallization grain coarsening.

Benefits of technology

It is achieved that a complete and fine recrystallization structure is obtained under the condition of an extrusion temperature of 420°C, which improves the strength and toughness of the magnesium alloy, and the yield strength, tensile strength and elongation are 340MPa, 382MPa and 25.2%, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571228A_ABST
    Figure CN119571228A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy processing, and particularly relates to a preparation method of a complete and fine recrystallized Mg-Y-Zn magnesium alloy. According to the method, homogeneous Mg-Y-Zn magnesium alloy is sequentially subjected to first-pass small-extrusion-ratio extrusion with the extrusion ratio being 4 / 1 and second-pass large-extrusion-ratio extrusion with the extrusion ratio being 25 / 1; the temperature of the two times of extrusion is 420 DEG C, and the extrusion speed is 0.4 mm / s; the atomic ratio of Y to Zn in the Mg-Y-Zn magnesium alloy is 2 / 1; according to the method, the problem that the size of recrystallized grains is seriously coarsened along with temperature increase in the single-pass extrusion process is solved, a complete and fine recrystallized structure is obtained, and meanwhile the strength and toughness of the magnesium alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy processing, and relates to a method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy. Background Art

[0002] Mg-Y-Zn magnesium alloys have attracted much attention in the fields of weight reduction such as automobiles, aircraft, aerospace, military industry, and hydrogen storage energy due to their excellent mechanical properties. However, how to achieve a synergistic improvement in their strength and toughness is still a huge challenge for Mg-Y-Zn magnesium alloys. At present, the main methods that can improve the strength and toughness of magnesium alloys include solution treatment, aging treatment, alloying and microalloying modification, external electromagnetic field and power ultrasonic treatment technology, plastic deformation technology, and 3D printing technology.

[0003] Extrusion is a commonly used plastic deformation technology in industry and is also the most effective method to improve the mechanical properties of metal materials. Dynamic recrystallization is one of the key factors that determine the performance of Mg-Y-Zn wrought magnesium alloys. This is because micron, submicron, and nano recrystallized grains can be obtained by low temperature, slow speed, or small extrusion ratio extrusion, so that the magnesium alloy can obtain higher strength. However, low temperature, slow speed, and small extrusion ratio extrusion will lead to the appearance of an incompletely recrystallized structure, thereby reducing the toughness of the magnesium alloy. Although the increase in extrusion temperature, speed, and extrusion ratio will promote the formation of a completely recrystallized structure and improve the toughness of the alloy, the increase in extrusion temperature, speed, and extrusion ratio will also cause severe coarsening of recrystallized grains, resulting in a significant reduction in the strength of the alloy. At present, it is difficult for Mg-Y-Zn wrought magnesium alloys to achieve simultaneous improvement in strength and toughness. Therefore, a complete and fine recrystallized structure has become an urgent need to overcome the bottleneck of high strength and high toughness trade-offs in Mg-Y-Zn wrought magnesium alloys.

[0004] Existing plastic deformation technologies, including extrusion, rolling, forging, equal channel angular extrusion, high pressure torsion, reciprocating extrusion, etc., can obtain fine grains and ultrafine grains, and prepare high-strength and ultra-high-strength magnesium alloys. However, these plastic deformation technologies have certain limitations, and it is difficult to obtain a complete and fine recrystallized structure, especially the structure of high-strength and ultra-high-strength magnesium alloys often presents serious incomplete recrystallization characteristics, and the proportion of recrystallization is very small, which makes it show extremely low toughness. More importantly, for high-strength and ultra-high-strength magnesium alloys, this type of plastic deformation technology requires larger tonnage equipment, more complex mold structures and special machinery and equipment, which is difficult to use for industrial applications. For example, the Chinese invention patent (CN112547826A) discloses a high-performance magnesium alloy forming method for preparing a gradient temperature and rate field, but the total number of forming passes N of this method is ≥2. A Chinese invention patent (CN111482545A) discloses a high-strength and high-toughness magnesium alloy layer-wrap forging method with multi-scale precipitation strengthening effect. This method requires multi-mode and multi-pass forging processing, and can only form a thin gradient structure layer on the sample surface. A Chinese invention patent (CN102127723A) discloses a deformation heat treatment method for obtaining a high-strength and high-toughness magnesium alloy. This method combines multi-axial deformation and artificial aging to produce a high-strength and high-toughness magnesium alloy, but the prepared high-performance AZ91 magnesium alloy requires at least 8 deformation passes, and the prepared high-performance AZ61 magnesium alloy requires at least 4 deformation passes. Summary of the invention

[0005] The present invention overcomes the shortcomings of the prior art and proposes a method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy; the present invention is achieved through the following technical solutions: A method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy, wherein the homogeneous Mg-Y-Zn magnesium alloy is sequentially subjected to a first pass of small extrusion ratio extrusion and a second pass of large extrusion ratio extrusion; the Y / Zn atomic ratio in the Mg-Y-Zn magnesium alloy is 2 / 1; The extrusion ratio of the first small extrusion ratio extrusion is 4 / 1, the extrusion temperature is 420°C, and the extrusion speed is 0.4mm / s; The extrusion ratio of the second high extrusion ratio extrusion is 25 / 1, the extrusion temperature is 420° C., and the extrusion speed is 0.4 mm / s.

[0006] Preferably, the homogeneous Mg-Y-Zn magnesium alloy is a magnesium alloy test bar obtained through alloy preparation, alloy smelting, alloy casting and solidification, and homogenization treatment.

[0007] More preferably, the alloy smelting is to set the temperature of the resistance furnace to 400°C, add the preheated magnesium block into the crucible to obtain a magnesium alloy melt; then raise the temperature of the resistance furnace to 720°C, and keep the temperature constant to completely melt the magnesium block; then add the preheated zinc block, raise the temperature of the resistance furnace to 780°C, skim off the slag, add the preheated yttrium particles, and after the insulation treatment, reduce the furnace temperature to 750°C for refining.

[0008] More preferably, the alloy casting and solidification is to keep the temperature at 750°C for 30-40 minutes, then lower the furnace temperature to 730°C, remove the slag, and cast the magnesium melt into a preheated metal mold; after the alloy melt is completely solidified in the air and naturally cools to room temperature as the mold temperature, knock the sample out of the mold to obtain a Mg-Y-Zn magnesium alloy test bar.

[0009] More preferably, the homogenization treatment is carried out in a tubular furnace, the homogenization treatment temperature is 500° C., and the homogenization treatment time is 30 hours.

[0010] Preferably, the first extrusion with a small extrusion ratio and the second extrusion with a large extrusion ratio are both performed using a vertical extruder, the extrusion method is forward extrusion, and the extrusion die includes an extrusion die, an extrusion gasket, an extrusion rod and an extrusion sleeve.

[0011] Preferably, the Mg—Y—Zn magnesium alloy obtained after the second high extrusion ratio extrusion is subjected to water quenching treatment.

[0012] Preferably, the atomic ratio at.% of the Mg-Y-Zn magnesium alloy is Mg 98.5 Yj Y 0.5 .

[0013] The present invention aims at the problem of mismatch between strength and toughness of Mg-Y-Zn deformed magnesium alloys, selects a 95.17Mg-3.53Y-1.30Zn (mass percentage) magnesium alloy as the base material, and uses a two-pass cumulative large extrusion ratio (100 / 1) extrusion forming preparation technology to overcome the problem of serious coarsening of recrystallized grains with increasing temperature during a single-pass extrusion process, obtains a complete and fine recrystallized structure, and improves the strength and toughness of the magnesium alloy. At the same time, the present invention sets up a single-pass extrusion comparison test at different temperatures, studies the influence of extrusion temperature on recrystallization behavior and alloy mechanical properties, and explores the reason why a complete and fine recrystallized structure is obtained by two-pass cumulative large extrusion ratio extrusion.

[0014] The beneficial effects of the present invention compared with the prior art are as follows: (1) The present invention uses only two extrusion deformations, and the cumulative extrusion ratio reaches 100, so that the 95.17Mg-3.53Y-1.30Zn magnesium alloy obtains a complete and fine recrystallized structure at an extrusion temperature of 420°C, and the recrystallized grain size is only 1.68μm.

[0015] (2) The present invention dynamically precipitates a large amount of high-density fine 14H-LPSO structural strengthening phase in the 95.17Mg-3.53Y-1.30Zn magnesium alloy through a specific two-pass cumulative large extrusion ratio extrusion deformation. The precipitated phase can produce a significant grain boundary pinning effect on recrystallization, which can greatly inhibit the further growth of recrystallization, thereby obtaining a complete and fine recrystallized structure.

[0016] (3) The present invention uses a specific two-pass cumulative large extrusion ratio extrusion deformation to make the yield strength, tensile strength and elongation of the 95.17Mg-3.53Y-1.30Zn magnesium alloy reach 340MPa, 382MPa and 25.2% respectively, showing an excellent high-strength and high-toughness match. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of thermal processing of casting 95.17Mg-3.53Y-1.30Zn alloy in Example 1 and Comparative Example 1; Figure 2 Schematic diagram of the extrusion die for two extrusion ratios in Example 1; Figure 3 The 95.17Mg-3.53Y-1.30Zn alloy test bars obtained after extrusion of Example 1 and Comparative Example 1; Figure 4 This is a scanning electron microscopy (TEM) photograph of the first small-angle extruded 95.17Mg-3.53Y-1.30Zn alloy in Example 1; Figure 5 Electron backscatter diffraction (EBSD) microstructure photos of 95.17Mg-3.53Y-1.30Zn alloy extruded by single pass in comparative example 1 and by two passes with a large cumulative extrusion ratio in example 1; Figure 6 Transmission electron microscopy (TEM) photos of the 95.17Mg-3.53Y-1.30Zn alloy extruded at 420°C in two passes with a large extrusion ratio in Example 1; (a) fine 14H-LPSO phase morphology, (b) selected diffraction spots of 14H-LPSO structure; Figure 7 Room temperature tensile stress-strain curves of extruded 95.17Mg-3.53Y-1.30Zn alloys of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.

[0019] Example 1 This embodiment proposes a method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy, and the extrusion die is simple, the processing and manufacturing cost is low, and the practicability is strong. First, a cast 95.17Mg-3.53Y-1.30Zn (mass percentage) magnesium alloy is used as the initial material, and then a two-pass cumulative large extrusion ratio extrusion deformation process (total extrusion ratio is 100 / 1) is adopted. While ensuring complete recrystallization, the effective pinning effect of the dynamic precipitation high-density fine 14H-LPSO structure relative to the grain boundary migration is utilized to overcome the problem of severe coarsening of the recrystallized grain size during the single-pass large extrusion ratio extrusion process, and a complete and fine recrystallized structure is obtained, thereby simultaneously improving the strength and toughness of the magnesium alloy.

[0020] It includes the following two units: S1. Preparation of smelting 95.17Mg-3.53Y-1.30Zn magnesium alloy and casting solidification unit S1.1. Alloy preparation The mass ratio wt.% is 95.17Mg-3.53Y-1.30Zn (atomic ratio at.% is Mg 98.5 Yj Y 0.5 ) magnesium alloy as the parent material, because under the specific condition that the Y / Zn atomic ratio is 2 / 1, a large number of long strips of 14H-LPSO structural strengthening phases can be formed in the subsequent first small extrusion ratio extrusion process to inhibit the nucleation and growth of dynamic recrystallization in the magnesium matrix. Prepare the required raw materials by weighing according to the mass ratio: including magnesium blocks (Mg) with a purity of 99.99wt.%, yttrium particles (Y), and zinc blocks (Zn). The actual chemical composition range of the alloy is: Y: 3.2~3.7wt.%, Zn: 1.0~1.5wt.%, and the rest is Mg. After the raw materials are polished to remove the oxide layer on the surface, they are placed in a drying oven together with covering agents, casting molds, slag removal and stirring tools for drying and preheating.

[0021] S1.2 Alloy smelting The magnesium alloy is melted by a resistance furnace. When the temperature of the resistance furnace is set to 400°C, the preheated magnesium block is added to the crucible, and the preheated salt covering agent is evenly sprinkled on the surface of the crucible. The crucible with the magnesium block is clamped into the resistance furnace, and argon (Ar2) is introduced into the furnace at the same time. The present invention adopts a salt covering agent + Ar2 composite protection method for melt protection to prevent oxidation and combustion of the magnesium melt, and obtain a high-quality clean magnesium alloy melt. When the temperature of the resistance furnace rises to 720°C, the constant temperature is kept for 30 minutes to ensure that the magnesium block is completely melted. After the magnesium block is melted, the slag is removed, the preheated zinc block is added, and the covering agent is evenly sprinkled and the temperature is raised. When the temperature of the resistance furnace rises to 780°C, the slag is removed, the preheated yttrium particles are added, the covering agent is sprinkled after stirring, the furnace temperature is raised to 780°C and kept warm. After keeping warm for 15 minutes, the furnace temperature is reduced to 750°C, the slag is removed, and a refining agent is sprinkled into the magnesium melt for refining. After refining, the furnace temperature was raised to 750°C, and the magnesium melt was allowed to stand at 750°C for 30 minutes.

[0022] S1.3 Alloy casting and solidification After keeping at 750℃ for 30 minutes, the furnace temperature was lowered to 730℃, the slag was removed, and the magnesium melt was cast into a preheated metal mold (200℃). After the alloy melt was completely solidified in the air and naturally cooled to room temperature with the mold temperature, the sample was knocked out of the mold to obtain a 95.17Mg-3.53Y-1.30Zn cast magnesium alloy test bar with a diameter of 82mm and a height of 200mm.

[0023] S2, cumulative large extrusion ratio extrusion 95.17Mg-3.53Y-1.30Zn magnesium alloy unit S2.1. Homogenization Direct hot extrusion of cast magnesium alloy test bars is prone to problems such as uneven structure and overheating. Secondly, homogenization treatment can make Y and Zn atoms dissolve into the Mg matrix to the maximum extent, thereby obtaining a supersaturated solid solution. Therefore, in order to improve the structure of magnesium alloys and enhance their subsequent plastic deformation ability, the cast alloy test bars need to be homogenized. In the present invention, the homogenization treatment is carried out in a tubular furnace, and the cast magnesium alloy test bars are covered with MgO powder, placed in a tubular furnace, and then evacuated, and then Ar2 is continuously introduced for gas protection. The homogenization temperature is set to 500°C, and the homogenization time is set to 30 hours. After the set time is completed, turn off the power, quickly take out the magnesium alloy test bar from the furnace for water quenching, and obtain a homogenized magnesium alloy test bar.

[0024] S2.2, first pass small extrusion ratio extrusion See also Figure 2 , Figure 3 and Figure 4, a vertical extruder was selected, and the extrusion method was positive extrusion. The extrusion die included an extrusion die, an extrusion gasket, an extrusion rod and an extrusion sleeve, and the maximum extrusion force was 500 tons. For the first extrusion, a small extrusion ratio extrusion die with an extrusion ratio of 4 / 1 was selected, the extrusion temperature was 420℃, the extrusion speed was 0.4mm / s, the extrusion billet diameter was 80mm, and the height was 50mm. Before extrusion, the homogeneous magnesium alloy test bar was placed in a heat treatment furnace for preheating, and the extrusion die was preheated in a heat preservation furnace provided on the extruder workbench. After the test bar and the extrusion die were kept at the extrusion temperature (420℃) for 1 hour, they were extruded at the set extrusion temperature (420℃) and extrusion speed (0.4mm / s), and the extruded magnesium alloy test bar was water quenched. Through the first extrusion with a small extrusion ratio (4 / 1), an extruded test bar with a diameter of 40mm was obtained.

[0025] In the present invention, a large amount of long strip 14H-LPSO structural phases are precipitated in the 95.17Mg-3.53Y-1.30Zn magnesium alloy matrix by the first pass of small extrusion ratio extrusion. The large amount of precipitation of long strip 14H-LPSO structural phases can seriously inhibit the nucleation and growth of dynamic recrystallization in the magnesium matrix.

[0026] S2.3, the second pass of high extrusion ratio extrusion In the second extrusion, a large extrusion ratio extrusion die with an extrusion ratio of 25 / 1 was selected, the extrusion temperature was 420℃, the extrusion speed was 0.4mm / s, the extruded billet diameter was 40mm, and the height was 35mm. Before extrusion, the magnesium alloy test bar extruded in the first pass was placed in a heat treatment furnace for preheating, and the extrusion die was preheated in a heat preservation furnace provided on the extruder workbench. After the test bar and the extrusion die were kept at 420℃ for 1 hour, they were extruded at the set extrusion temperature (420℃) and extrusion speed (0.4mm / s), and the extruded magnesium alloy test bar was water quenched. Through the first pass of small extrusion ratio extrusion with an extrusion ratio of 4 / 1 and the second pass of large extrusion ratio extrusion with an extrusion ratio of 25 / 1, the cumulative large extrusion ratio extrusion forming preparation of magnesium alloy with a total extrusion ratio of 100 / 1 was achieved, and an extruded test bar with a diameter of 8mm was obtained.

[0027] In the present invention, the second high extrusion ratio extrusion will promote complete recrystallization in the 95.17Mg-3.53Y-1.30Zn magnesium alloy matrix. At the same time, the high extrusion ratio extrusion transforms the long strip 14H-LPSO structure phase precipitated in the first pass into a fine 14H-LPSO structure phase inside the recrystallized grains. The fine 14H-LPSO structure phase can seriously hinder the migration of grain boundaries, overcome the abnormal growth of dynamic recrystallization, and promote a complete and fine recrystallized structure.

[0028] Comparative Example 1 Single-pass extrusion comparison test: See also Figure 1 The present invention designs three groups of single-pass extrusion comparison tests at different extrusion temperatures. The steps different from those in Example 1 are as follows (the rest of the steps are the same): An extrusion die with an extrusion ratio of 25 / 1 was selected. The extrusion temperatures were 350℃, 380℃, and 420℃, respectively. The extrusion speed was 0.4mm / s. The diameter of the extruded billet was 40mm and the height was 35mm. Before extrusion, the homogeneous magnesium alloy test bar was placed in a heat treatment furnace for preheating treatment, and the extrusion die was preheated in a holding furnace provided on the workbench of the extruder. After the test bar and the extrusion die were kept at the extrusion temperature (350℃, 380℃, and 420℃) for 1 hour, they were extruded at the set extrusion temperature (350℃, 380℃, and 420℃) and extrusion speed (0.4mm / s), and the extruded magnesium alloy test bar was water quenched. An extruded test bar with a diameter of 8mm was obtained by a single-pass extrusion with an extrusion ratio of 25 / 1, see Figure 3 The conditions for the three groups of single-pass extrusion tests are as follows: (1) The extrusion ratio is 25 / 1, the extrusion speed is 0.4 mm / s, and the extrusion temperature is 350 °C; (2) Extrusion ratio is 25 / 1, extrusion speed is 0.4 mm / s, and extrusion temperature is 380 °C; (3) Extrusion ratio is 25 / 1, extrusion speed is 0.4 mm / s, and extrusion temperature is 420 °C; For comparative analysis, see Figures 5 to 7 : (1) Example 1 only uses two extrusions to deform, and the cumulative extrusion ratio reaches 100, so that the 95.17Mg-3.53Y-1.30Zn magnesium alloy obtains a complete and fine recrystallized structure at an extrusion temperature of 420°C, and the recrystallized grain size is only 1.68μm. Compared with the two-pass extrusion, in the single-pass extrusion process, when the extrusion temperature increases from 350°C to 420°C, the 95.17Mg-3.53Y-1.30Zn magnesium alloy obtains a complete recrystallized structure, but the increase in temperature causes the recrystallized grains to grow abnormally, and the grain size increases from 1.66μm (350°C) to 6.12μm (420°C).

[0029] (2) In Example 1 of the present invention, a large amount of high-density fine 14H-LPSO structural strengthening phase is dynamically precipitated in the 95.17Mg-3.53Y-1.30Zn magnesium alloy through specific two-pass cumulative large extrusion ratio extrusion deformation. The precipitated phase can produce a significant grain boundary pinning effect on recrystallization, which can greatly inhibit the further growth of recrystallization, thereby obtaining a complete and fine recrystallized structure.

[0030] (3) In Example 1 of the present invention, the yield strength, tensile strength and elongation of the 95.17Mg-3.53Y-1.30Zn magnesium alloy can reach 340MPa, 382MPa and 25.2% respectively through a specific two-pass cumulative large extrusion ratio extrusion deformation, showing an excellent high-strength and high-toughness match. Compared with the two-pass extrusion, the yield strength and tensile strength of the 95.17Mg-3.53Y-1.30Zn magnesium alloy decrease from 326 / 332MPa to 236 / 278MPa, while the elongation increases from 7.7% to 20.6%, showing an obvious inverted relationship between strength and toughness.

[0031] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.

Claims

1. A method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy, characterized in that: The homogeneous Mg-Y-Zn magnesium alloy is sequentially subjected to a first pass of small extrusion ratio extrusion and a second pass of large extrusion ratio extrusion; the Y / Zn atomic ratio in the Mg-Y-Zn magnesium alloy is 2 / 1; The extrusion ratio of the first small extrusion ratio extrusion is 4 / 1, the extrusion temperature is 420°C, and the extrusion speed is 0.4mm / s; The extrusion ratio of the second high extrusion ratio extrusion is 25 / 1, the extrusion temperature is 420° C., and the extrusion speed is 0.4 mm / s.

2. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 1, characterized in that: The homogeneous Mg-Y-Zn magnesium alloy is a magnesium alloy test rod obtained through alloy preparation, alloy smelting, alloy casting and solidification, and homogenization treatment.

3. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 2, characterized in that: The alloy smelting is to set the temperature of the resistance furnace to 400°C, add the preheated magnesium block into the crucible to obtain a magnesium alloy melt; then raise the temperature of the resistance furnace to 720°C, and keep the temperature constant to completely melt the magnesium block; then add the preheated zinc block, raise the temperature of the resistance furnace to 780°C, skim off the slag, add the preheated yttrium particles, and after heat preservation, reduce the furnace temperature to 750°C for refining.

4. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 2, characterized in that: The alloy casting and solidification is to keep the temperature at 750°C for 30-40 minutes, then lower the furnace temperature to 730°C, remove the slag, and cast the magnesium melt into a preheated metal mold; after the alloy melt is completely solidified in the air and naturally cools to room temperature as the mold temperature, the sample is knocked out of the mold to obtain a Mg-Y-Zn magnesium alloy test bar.

5. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 2, characterized in that: The homogenization treatment is carried out in a tubular furnace, the homogenization treatment temperature is 500° C., and the homogenization treatment time is 30 hours.

6. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 1, characterized in that: The first extrusion with a small extrusion ratio and the second extrusion with a large extrusion ratio are both performed by a vertical extruder, the extrusion method is forward extrusion, and the extrusion die includes an extrusion die, an extrusion gasket, an extrusion rod and an extrusion sleeve.

7. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 1, characterized in that: The Mg-Y-Zn magnesium alloy obtained after the second high extrusion ratio extrusion is water quenched.

8. The method for preparing a completely and finely recrystallized Mg-Y-Zn magnesium alloy according to claim 1, characterized in that: The atomic ratio at.% of Mg-Y-Zn magnesium alloy is Mg 98.5 Yj Y 0.5 .

Citation Information

Patent Citations

  • Thermomechanical treatment method for obtaining high-strength and high-toughness magnesium alloy

    CN102127723A

  • Method and system for preparing magnesium alloy bar through layered winding and rotary forging

    CN111482545A

  • Gradient temperature and rate field type magnesium alloy forming method

    CN112547826A

  • Low-rare-earth high-strength deforming magnesium alloy and preparation method thereof

    CN105543603A

  • Preparation method of low-rare-earth high-strength Mg98.5 Y1Zn0.5 magnesium alloy

    CN115627399A

Cited By

  • Preparation method of rare earth magnesium alloy bar

    CN121042386A

  • A method for producing a rare earth magnesium alloy rod

    CN121042386B